2019
DOI: 10.1002/brb3.1223
|View full text |Cite
|
Sign up to set email alerts
|

Circle of Willis variations in migraine patients with ischemic stroke

Abstract: Objectives Migraine is a risk factor for stroke, which might be explained by a higher prevalence in anatomical variants in the circle of Willis (CoW). Here, we compared the presence of CoW variants in patients with stroke with and without migraine. Materials and Methods Participants were recruited from the prospective Dutch acute Stroke Study. All participants underwent CT angiography on admission. Lifetime migraine history was assessed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
2
3
0
1
Order By: Relevance
“…Due to the small size of CoW segments, the true number of patients with a complete CoW might be higher. Nevertheless, the amount of different CoW variants we found was in accordance with other studies using different methods [ 9 , 10 ]. Furthermore, the restriction to an LVO stroke cohort might have influenced or overlapped the effect of CoW variants on outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Due to the small size of CoW segments, the true number of patients with a complete CoW might be higher. Nevertheless, the amount of different CoW variants we found was in accordance with other studies using different methods [ 9 , 10 ]. Furthermore, the restriction to an LVO stroke cohort might have influenced or overlapped the effect of CoW variants on outcome.…”
Section: Discussionsupporting
confidence: 92%
“…This led to the development of four vascular models of presumed flow compensation in cases of MCA‐M1‐occlusion stroke (Figure 1 ) according to previously described flow dynamics in patients with LVO [ 5 , 6 , 7 ]. We found that a high (82.4%) proportion of patients with MCA‐M1‐occlusion stroke had an incomplete or hypoplastic CoW affecting predominantly the posterior circulation (77.2%), which is in line with previous data [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another [20] showed a significantly higher proportion of complete fetal-type PCA in migraineurs without aura. Only one previous study [21] investigated circle of Willis variations and migraine in stroke populations, which had a similar design to ours but negative results. First, this inconsistency might be interpreted by differences in criteria assessing the fetal-type PCA.…”
Section: Discussionmentioning
confidence: 76%
“…De qualquer maneira, evidenciase que padrões de fluxo alterados e altas taxas de fluxo colateral são encontrados perto das oclusões em muitos casos de AVE (CHIEN, 2017). Atualmente, problemas relacionados a doenças cerebrovasculares estão aumentando, e o AVE é a quarta principal causa de morte e o evento mais comum de perda de autonomia e qualidade de vida (HAMMING, 2019).…”
Section: Introductionunclassified